Orthodontic treatment of mandibular anterior crowding (Bangladesh Journal of Medical Science, 2009)
This paper concerns orthodontic treatment of a 17 years old Bangladeshi female with a class I malocclusion along with anterior crowding in the mandibular arch. Orthodontic treatment carried out with preadjusted Roth type (018 slot) fixed brackets with labial flaring of the mandibular incisors to accomplish the treatment. The esthetics and occlusion were maintained after retention. Key words: Crowding, malocclusion, labial flaring. doi: 10.3329/bjms.v8i1.3188 Bangladesh Journal of Medical Science Vol.8 No. 1-2; 2009 33-36